Resin composition and molded article

By adjusting the relative viscosity of the phthalamide-based polyamide resin and adding reinforcing fibers, the problem of insufficient crystallization of the polyamide resin composition during low-temperature molding is solved, and the effect of fast molding cycle and excellent appearance of the molded product is achieved.

CN119630742APending Publication Date: 2025-03-14MITSUBISHI GAS CHEM CO INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380055593.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-25
Filing Date
2023-06-19
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing polyamide resin compositions are insufficiently crystallized during low-temperature mold molding, and the use of fatty acid metal salts and inorganic crystallization nucleating agents are required, which limits the expansion of their application.

Method used

By adjusting the relative viscosity of the phthalamine-based polyamide resin to 1.6 to 2.4 and containing 10 to 300 parts by mass of reinforcing fibers, the flowability and crystallization rate of the resin composition are optimized.

Benefits of technology

The molding cycle is shortened and the appearance of the molded product is optimized, and molded products with mechanical strength, impact resistance, gas barrier, low dissolution, chemical resistance and low water absorption are provided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005253421930000261
    Figure BDA0005253421930000261
  • Figure BDA0005253421930000271
    Figure BDA0005253421930000271
  • Figure BDA0005253421930000281
    Figure BDA0005253421930000281
Patent Text Reader

Abstract

A resin composition which contains 10-300 parts by mass of reinforcing fibers per 100 parts by mass of a xylylenediamine-based polyamide resin that contains a diamine unit and a dicarboxylic acid unit, the diamine unit containing 70 mol% or more of a constituent unit derived from xylylenediamine, and the dicarboxylic acid unit containing 70 mol% or more of a constituent unit derived from xylylenediamine. The dicarboxylic acid unit contains 70 mol% or more of a structural unit derived from an alpha, omega-linear aliphatic dicarboxylic acid having 11 to 20 carbon atoms, and the xylylenediamine polyamide resin has a relative viscosity of 1.6 to 2.4.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a resin composition and a molded product, and in particular to a resin composition with a polyamide resin as a main component. Background Art

[0002] Resin molded products are used for the purpose of reducing the weight and cost of metal molded products. In particular, polyamide resins, which have excellent properties such as heat resistance, chemical resistance, rigidity, wear resistance, and moldability, are used in various applications.

[0003] Therefore, for reasons such as improving the fluidity of the resin composition, low-temperature molds are sometimes used for molding in injection molding and the like. However, if a low-temperature mold is used for molding, the crystallization of the polyamide resin is sometimes not fully carried out. In order to solve the above problems, a resin composition is disclosed in Patent Document 1, which comprises 80 to 150 parts by mass of inorganic fibers, 0.01 to 2 parts by mass of a fatty acid metal salt, and 0.1 to 10 parts by mass of an inorganic crystal nucleating agent relative to 100 parts by mass of a polyamide resin, wherein the polyamide resin is composed of a structural unit derived from a diamine and a structural unit derived from a dicarboxylic acid, wherein more than 70 mol% of the structural unit derived from the diamine is derived from xylenediamine, and more than 70 mol% of the structural unit derived from the dicarboxylic acid is derived from an aliphatic dicarboxylic acid having a carbon number of 9 to 18.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2022-054099 Summary of the invention

[0007] Problem that the invention aims to solve

[0008] The resin composition described in the above-mentioned patent document 1 is a resin composition that maintains high mechanical strength and can be fully crystallized even when a low-temperature mold is used for molding. However, in patent document 1, a fatty acid metal salt and an inorganic crystal nucleating agent are mixed. In the process of the use of polyamide resin compositions being increasingly expanded, a new polyamide resin composition that does not use fatty acid metal salts and inorganic crystal nucleating agents as essential components is required.

[0009] Here, in Example 6 of Patent Document 1, a resin composition is disclosed, which comprises: a polyamide resin (MP12) composed of m / p-phenylenediamine and dodecanedioic acid, glass fiber and talc. As in the aforementioned Example 6, if MP12 is used, the crystallization rate is promoted, and it can be expected to improve the molding cycle. However, the inventors have further studied and found that if the resin composition containing MP12 described in the aforementioned Example 6 is to be molded, the appearance of the molded product is sometimes poor. In particular, it is necessary to have a fast molding cycle and excellent appearance of the molded product according to the application.

[0010] The present invention aims to solve the above-mentioned problems and to provide a resin composition and a molded product which can provide a molded product having a fast molding cycle and excellent appearance.

[0011] Solutions for solving problems

[0012] The present inventors have conducted studies based on the above problems and have found that the above problems can be solved by adjusting the relative viscosity of a xylylenediamine-based polyamide resin such as a polyamide resin composed of xylylenediamine and dodecanedioic acid.

[0013] Specifically, the above-mentioned problems were solved by the following means.

[0014] <1> A resin composition comprising 10 to 300 parts by mass of reinforcing fibers relative to 100 parts by mass of a xylylenediamine-based polyamide resin,

[0015] The xylylenediamine-based polyamide resin comprises a diamine unit and a dicarboxylic acid unit, wherein the diamine unit comprises 70 mol% or more of a structural unit derived from xylylenediamine, and the dicarboxylic acid unit comprises 70 mol% or more of a structural unit derived from an α,ω-straight-chain aliphatic dicarboxylic acid having 11 to 20 carbon atoms, and

[0016] The relative viscosity of the xylylenediamine-based polyamide resin is 1.6 to 2.4.

[0017] <2> according to <1> The resin composition, wherein 70 mol % or more of the dicarboxylic acid units are derived from dodecanedioic acid and / or tetradecanedioic acid.

[0018] <3> according to <1> The resin composition, wherein 70 mol % or more of the dicarboxylic acid units are derived from dodecanedioic acid.

[0019] <4> according to <1> ~ <3> The resin composition described above, wherein 20 to 100 mol % of the diamine units are derived from m-xylylenediamine, and 80 to 0 mol % are derived from p-xylylenediamine.

[0020] <5> according to <1> The resin composition, wherein 70 mol% or more of the dicarboxylic acid units are derived from dodecanedioic acid and / or tetradecanedioic acid,

[0021] 20 to 100 mol% of the diamine units are derived from m-xylylenediamine, and 80 to 0 mol% are derived from p-xylylenediamine.

[0022] <6> according to <1> ~ <5> The resin composition described in any one of the preceding claims, wherein the difference between the terminal amino group concentration and the terminal carboxyl group concentration (|terminal amino group concentration−terminal carboxyl group concentration|) of the xylylenediamine-based polyamide resin is 10 μmol / g or more.

[0023] <7> A molded product, which is composed of <1> ~ <6> The resin composition described in any one of the above is formed.

[0024] Effects of the Invention

[0025] According to the present invention, a resin composition and a molded product capable of providing a molded product having a fast molding cycle and excellent appearance can be provided. DETAILED DESCRIPTION

[0026] Hereinafter, a mode for implementing the present invention (hereinafter, simply referred to as "this embodiment") will be described in detail. It should be noted that the following this embodiment is an example for explaining the present invention, and the present invention is not limited to this embodiment.

[0027] In addition, in this specification, "to" is used to mean that the numerical values ​​described before and after it are included as a lower limit and an upper limit.

[0028] In this specification, various physical property values ​​and characteristic values ​​are assumed to be values ​​at 23° C. unless otherwise specified.

[0029] Unless otherwise specified in this specification, the number average molecular weight can be measured according to the description in paragraph 0047 of JP-A-2018-165298, and the content thereof is incorporated into this specification.

[0030] Unless otherwise specified, the melting point (Tm) is described as a value measured by differential scanning calorimetry (DSC) in accordance with ISO 11357. Specifically, it can be measured according to the description of paragraph 0036 of International Publication No. 2016 / 084475, and the content thereof is incorporated into the present specification.

[0031] When the measurement methods and the like described in the specifications shown in this manual differ by year, they are based on the specifications as of January 1, 2022 unless otherwise specified.

[0032] The resin composition of the present embodiment is characterized in that it contains reinforcing fibers in a ratio of 10 to 300 parts by mass relative to 100 parts by mass of a xylylenediamine-based polyamide resin, the aforementioned xylylenediamine-based polyamide resin contains a diamine unit and a dicarboxylic acid unit, the aforementioned diamine unit contains more than 70 mol% of a structural unit derived from xylylenediamine, the aforementioned dicarboxylic acid unit contains more than 70 mol% of a structural unit derived from an α,ω-straight-chain aliphatic dicarboxylic acid having a carbon number of 11 to 20, and the aforementioned xylylenediamine-based polyamide resin has a relative viscosity of 1.6 to 2.4. By forming such a structure, a resin composition that can provide a molded product with a fast molding cycle and excellent appearance can be provided. That is, in the present embodiment, in order to speed up the molding cycle, a xylylenediamine-based polyamide resin containing a structural unit derived from an α,ω-straight-chain aliphatic dicarboxylic acid having a carbon number of 11 to 20 is used as a polyamide resin. However, it is known that if reinforcing fibers are compounded in such a xylylenediamine-based polyamide resin, when the relative viscosity of the xylylenediamine-based polyamide resin is increased, the fluidity of the reinforcing fibers is poor and the appearance of the molded product is poor. Therefore, it is presumed that in the present embodiment, by using a xylylenediamine-based polyamide resin having a slightly low relative viscosity, the fluidity of the polyamide resin composition containing reinforcing fibers can be improved, and the appearance of the obtained molded article can be improved.

[0033] Furthermore, the resin composition of the present embodiment can provide a molded product having excellent mechanical strength such as flexural modulus and impact resistance. In addition, the resin composition of the present embodiment can provide a molded product having excellent gas barrier properties, a small amount of eluted matter, excellent chemical resistance, low water absorption, and a fast crystallization rate. These are achieved by using a predetermined xylylenediamine-based polyamide resin.

[0034] <Xylylenediamine-based polyamide resin>

[0035] The resin composition of the present embodiment includes a xylylenediamine polyamide resin (sometimes referred to as "xylylenediamine polyamide resin" in this specification), wherein the xylylenediamine polyamide resin includes a diamine unit and a dicarboxylic acid unit, wherein the diamine unit includes 70 mol% or more of a structural unit derived from xylylenediamine, and the dicarboxylic acid unit includes 70 mol% or more of a structural unit derived from an α,ω-straight-chain aliphatic dicarboxylic acid having 11 to 20 carbon atoms, and the relative viscosity is 1.6 to 2.4. By using such a xylylenediamine polyamide resin, a resin composition that can provide a molded product with a fast molding cycle and excellent appearance can be obtained.

[0036] More preferably, 75 mol% or more, further preferably 80 mol% or more, further preferably 90 mol% or more, still further preferably 95 mol% or more, and particularly preferably 99 mol% or more of the diamine-derived structural units of the xylylenediamine-based polyamide resin are derived from xylylenediamine (preferably p-xylylenediamine and / or m-xylylenediamine).

[0037] In xylylenediamine, more specifically, preferably 20 to 100 mol% of the structural units derived from diamine are structural units derived from meta-xylylenediamine, preferably 50 to 100 mol% of the structural units derived from diamine are structural units derived from meta-xylylenediamine, more preferably 55 to 80 mol% of the structural units derived from diamine are structural units derived from meta-xylylenediamine, and 45 to 20 mol% of the structural units derived from diamine are structural units derived from p-xylylenediamine. By setting the proportion of p-xylylenediamine to 20 mol% or more, the crystallization rate becomes faster, and there is a tendency that the impact resistance of the obtained molded article is improved. In addition, by reducing the proportion of meta-xylylenediamine, the amount of eluted matter from the molded article can be reduced.

[0038] In the xylylenediamine-based polyamide resin, the total amount of the structural units derived from p-xylylenediamine and the structural units derived from m-xylylenediamine preferably accounts for 80 mol% or more of the structural units derived from diamine, more preferably 85 mol% or more, further preferably 90 mol% or more, further preferably 95 mol% or more, further preferably 98 mol% or more, and further preferably 99 mol% or more. The upper limit of the total amount of the structural units derived from p-xylylenediamine and the structural units derived from m-xylylenediamine is 100 mol%.

[0039] Examples of diamines other than meta-xylylenediamine and para-xylylenediamine that can be used as the raw material diamine component of the xylylenediamine-based polyamide resin include aliphatic diamines such as tetramethylenediamine, pentamethylenediamine, 2-methylpentamethylenediamine, hexamethylenediamine, heptamethylenediamine, octamethylenediamine, nonamethylenediamine, decamethylenediamine, dodecamethylenediamine, 2,2,4-trimethyl-hexamethylenediamine, 2,4,4-trimethylhexamethylenediamine, and 1,3- Alicyclic diamines such as bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, 1,3-diaminocyclohexane, 1,4-diaminocyclohexane, bis(4-aminocyclohexyl)methane, 2,2-bis(4-aminocyclohexyl)propane, bis(aminomethyl)decalin, and bis(aminomethyl)tricyclodecane, and diamines having an aromatic ring such as bis(4-aminophenyl)ether, p-phenylenediamine, and bis(aminomethyl)naphthalene can be used alone or in combination of two or more.

[0040] On the other hand, preferably 75 mol% or more, more preferably 80 mol% or more, further preferably 90 mol% or more, even more preferably 95 mol% or more, and particularly preferably 99 mol% or more of the structural units derived from dicarboxylic acid of the xylylenediamine-based polyamide resin used in the present embodiment are derived from an α,ω-straight-chain aliphatic dicarboxylic acid having 11 to 20 carbon atoms (preferably an α,ω-straight-chain aliphatic dicarboxylic acid having 11 to 15 carbon atoms, and more preferably an α,ω-straight-chain aliphatic dicarboxylic acid having 12 to 14 carbon atoms).

[0041] Examples of the α,ω-straight-chain aliphatic dicarboxylic acid having 11 to 20 carbon atoms preferably used as the raw material dicarboxylic acid component of the xylylenediamine-based polyamide resin used in the present embodiment include undecanedioic acid, dodecanedioic acid, tridecanedioic acid, tetradecanedioic acid, pentadecanedioic acid, hexadecanedioic acid, heptadecanedioic acid, octadecanedioic acid, nonadecanedioic acid, and eicosanedioic acid. One or more of these may be used, and among these, dodecanedioic acid and / or tetradecanedioic acid are preferred.

[0042] As a preferred embodiment of the xylylenediamine-based polyamide resin in the present embodiment, 70 mol% or more (preferably 80 mol% or more, more preferably 90 mol% or more, and further preferably 95 mol% or more) of the structural units derived from dicarboxylic acid are derived from dodecanedioic acid and / or tetradecanedioic acid (preferably dodecanedioic acid). Dodecanedioic acid and xylylenediamine may also be raw materials derived from organisms (biomass raw materials).

[0043] Furthermore, in the above embodiment, preferably 20 to 100 mol% of the diamine units are derived from m-xylylenediamine and 80 to 0 mol% are derived from p-xylylenediamine, and more preferably 55 to 80 mol% of the diamine units are derived from m-xylylenediamine and 45 to 20 mol% are derived from p-xylylenediamine.

[0044] Examples of the dicarboxylic acid component other than the above-mentioned α,ω-straight-chain aliphatic dicarboxylic acid having 11 to 20 carbon atoms include phthalic acid compounds such as isophthalic acid, terephthalic acid, and phthalic acid, and isomers of naphthalene dicarboxylic acids such as 1,2-naphthalene dicarboxylic acid, 1,3-naphthalene dicarboxylic acid, 1,4-naphthalene dicarboxylic acid, 1,5-naphthalene dicarboxylic acid, 1,6-naphthalene dicarboxylic acid, 1,7-naphthalene dicarboxylic acid, 1,8-naphthalene dicarboxylic acid, 2,3-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, and 2,7-naphthalene dicarboxylic acid. These can be used alone or in combination of two or more.

[0045] It should be noted that the xylenediamine polyamide resin used in the present embodiment is composed of structural units derived from diamines and structural units derived from dicarboxylic acids as main components, but structural units other than these are not completely excluded, and of course, structural units derived from aliphatic aminocarboxylic acids such as lactams such as ε-caprolactam, laurolactam, aminocaproic acid, and aminoundecanoic acid may also be included. The main component here refers to the structural units that constitute the xylenediamine polyamide resin, and the total count of the structural units derived from diamines and the structural units derived from dicarboxylic acids is the largest among all structural units. In the present embodiment, the total of the structural units derived from diamines and the structural units derived from dicarboxylic acids in the xylenediamine polyamide resin preferably accounts for more than 90% by mass of all structural units, more preferably more than 95% by mass, further preferably more than 97% by mass, and further preferably more than 99% by mass.

[0046] The relative viscosity of the xylylenediamine polyamide resin used in the present embodiment is 1.6 to 2.4. By setting it above the lower limit, the crystallization rate of the polyamide resin tends to be faster. In addition, by setting it below the upper limit, the fluidity of the reinforcing fiber in the resin composition can be improved, and the appearance of the molded product can be improved.

[0047] The relative viscosity of the xylylenediamine polyamide resin used in the present embodiment is preferably 1.7 or more, more preferably 1.8 or more, further preferably 1.9 or more, and further preferably 2.0 or more. The relative viscosity of the xylylenediamine polyamide resin is preferably 2.3 or less, and more preferably 2.2 or less.

[0048] As a method for reducing the relative viscosity of the xylylenediamine polyamide resin, there is mentioned a method of using a slightly excessive amount of dicarboxylic acid or diamine instead of setting the molar ratio of the raw material diamine to the raw material dicarboxylic acid to 1:1 when synthesizing the xylylenediamine polyamide resin.

[0049] The relative viscosity of the xylylenediamine-based polyamide resin is measured according to the description in the examples described below.

[0050] In addition, in the present embodiment, the difference between the terminal amino group concentration and the terminal carboxyl group concentration of the xylylenediamine-based polyamide resin (|terminal amino group concentration - terminal carboxyl group concentration|) is preferably set to 10 μmol / g or more. The aforementioned |terminal amino group concentration - terminal carboxyl group concentration| is preferably 20 μmol / g or more, more preferably 30 μmol / g or more, and further preferably 40 μmol / g or more, and is preferably 170 μmol / g or less, more preferably 80 μmol / g or less, further preferably 70 μmol / g or less, and further preferably 60 μmol / g or less.

[0051] The terminal group concentration as a low-concentration terminal group in the terminal amino group concentration or the terminal carboxyl group concentration of the xylenediamine-based polyamide resin used in the present embodiment is preferably 80 μmol / g or less. By setting such an end group concentration, there is a tendency for the crystallization rate to become faster. The terminal group concentration as a low-concentration terminal group of the xylenediamine-based polyamide resin is more preferably 70 μmol / g or less, further preferably 60 μmol / g or less, further preferably 50 μmol / g or less, and further preferably 45 μmol / g or less. In addition, the lower limit of the terminal group concentration as a low-concentration terminal group of the aforementioned xylenediamine-based polyamide resin is preferably 10 μmol / g or more, more preferably 15 μmol / g or more, further preferably 20 μmol / g or more, further preferably 25 μmol / g or more, and further preferably 30 μmol / g or more. By setting it above the aforementioned lower limit, there is a tendency for the appearance of the obtained molded product to be further improved.

[0052] Among the terminal amino groups or terminal carboxyl groups of the xylylenediamine-based polyamide resin, the terminal amino group is preferably the terminal group having a low terminal group concentration.

[0053] The terminal group concentration of the xylylenediamine-based polyamide resin is measured according to the description in the Examples described below.

[0054] The melting point of the xylylenediamine-based polyamide resin used in the present embodiment is preferably 180° C. or higher, more preferably 200° C. or higher, and is preferably 280° C. or lower, more preferably 240° C. or lower.

[0055] The lower limit of the number average molecular weight (Mn) of the xylylenediamine polyamide resin used in the present embodiment is preferably 6,000 or more, more preferably 8,000 or more, and further preferably 10,000 or more, and is preferably 35,000 or less, more preferably 30,000 or less, and further preferably 25,000 or less. Within such a range, heat resistance, elastic modulus, dimensional stability, and molding processability become better.

[0056] The content of the xylenediamine polyamide resin used in the present embodiment in the resin composition of the present embodiment is preferably 40% by mass or more, more preferably 50% by mass or more, further preferably 60% by mass or more, and further preferably 64% by mass or more, and can be 68% by mass or more. By being set to above the aforementioned lower limit, there is a tendency for the surface appearance to become good. In addition, the content of the xylenediamine polyamide resin used in the present embodiment in the resin composition of the present embodiment is preferably 95% by mass or less, more preferably 90% by mass or less, further preferably 85% by mass or less, and further preferably 80% by mass or less in the resin composition. By being set to below the aforementioned upper limit, there is a tendency for the crystallization rate to become faster.

[0057] The resin composition of the present embodiment may contain only one type of the xylylenediamine-based polyamide resin used in the present embodiment, or may contain two or more types. When containing two or more types, the total amount is preferably within the above range.

[0058] The resin composition of the present embodiment may contain other polyamide resins other than the xylylenediamine-based polyamide resin used in the present embodiment without departing from the gist of the present invention.

[0059] The other polyamide resin is not particularly limited, and a known polyamide resin can be used. The polyamide resin may be an aliphatic polyamide resin or a semi-aromatic polyamide resin.

[0060] Examples of the aliphatic polyamide resin include polyamide 4, polyamide 46, polyamide 6, polyamide 66, polyamide 666, polyamide 610, polyamide 612, polyamide 11, and polyamide 12.

[0061] Examples of the semi-aromatic polyamide resin include terephthalic acid-based polyamide resins (polyamide 6T, polyamide 9T, polyamide 10T, polyamide 6I6T), and polyamide resins composed of xylylenediamine and an α,ω-straight-chain aliphatic dicarboxylic acid having less than 10 carbon atoms (MXD6, MP6, etc.).

[0062] When these other polyamide resins are contained, they are contained in a ratio of preferably 0.1 to 10% by mass, more preferably 0.1 to 5% by mass, based on the resin composition.

[0063] In the resin composition of the present embodiment, the total amount of the xylylenediamine polyamide resin and the reinforcing fibers used in the present embodiment preferably accounts for 90% by mass or more of the resin composition, more preferably 92% by mass or more, and further preferably 94% by mass or more.

[0064] <Reinforcement Fiber>

[0065] The resin composition of the present embodiment contains reinforcing fibers in a ratio of 10 to 300 parts by mass based on 100 parts by mass of the xylylenediamine-based polyamide resin used in the present embodiment. By containing reinforcing fibers, the mechanical strength of the obtained molded article can be improved.

[0066] Examples of the reinforcing fibers include carbon fibers and glass fibers, and glass fibers are preferably included.

[0067] The reinforcing fibers in the present embodiment refer to fibrous inorganic materials, and more specifically, preferably are chopped fibers obtained by bundling 1,000 to 10,000 reinforcing fibers and cutting them into a predetermined length.

[0068] The reinforcing fibers in this embodiment preferably have a number average fiber length of 0.5 to 10 mm, more preferably 1 to 5 mm. By using reinforcing fibers with such a number average fiber length, the mechanical strength can be further improved. The number average fiber length is calculated as follows: for an image obtained under observation with an optical microscope, the reinforcing fibers of the object for measuring the fiber length are randomly extracted and their long sides are measured, and the number average fiber length is calculated from the obtained measured value. The observation magnification is set to 20 times and the number of measurements is set to 1000 or more. It is roughly equivalent to the cut length.

[0069] In addition, the cross-section of the reinforcing fiber can be any shape such as a circle, an ellipse, an oblong, a rectangle, a shape obtained by combining a semicircle on two short sides of a rectangle, a cocoon shape, etc., preferably a circle. The meaning of the circle here is that, in addition to the circle in the mathematical sense, it also includes what is generally called a circle in the technical field of this embodiment.

[0070] The lower limit of the number average fiber diameter of the reinforcing fiber is preferably 4.0 μm or more, more preferably 4.5 μm or more, and further preferably 5.0 μm or more. The upper limit of the number average fiber diameter of the reinforcing fiber is preferably 15.0 μm or less, more preferably 12.0 μm or less. By using a reinforcing fiber with a number average fiber diameter in such a range, a resin molded product with better plating properties can be obtained even after wet heat treatment. Furthermore, even if the resin molded product is stored for a long time and the heat treatment is carried out for a long time, high plating properties can be maintained. It should be noted that the number average fiber diameter of the reinforcing fiber is calculated as follows: for the image obtained under the observation of an electron microscope, the glass fiber of the object of measuring the fiber diameter is randomly extracted, and the fiber diameter is measured near the central part, and the measured value is calculated. The observation magnification is set to 1000 times and the number of measurements is set to 1000 or more. The number average fiber diameter of the glass fiber with a cross section other than a circle is recorded as the number average fiber diameter when converted to a circle with the same area as the cross section.

[0071] Next, the glass fiber preferably used in the present embodiment will be described.

[0072] The glass fiber used is obtained by melt-spinning commonly available glasses such as E glass (Electrical glass), C glass (Chemical glass), A glass (Alkali glass), S glass (High strength glass), D glass, R glass, and alkali-resistant glass.

[0073] The glass fiber used in the present embodiment is preferably surface treated with a surface treatment agent such as a silane coupling agent such as γ-methacryloxypropyl trimethoxysilane, γ-glycidyloxypropyl trimethoxysilane, and γ-aminopropyl triethoxysilane. The amount of the surface treatment agent attached is preferably 0.01 to 1% by mass of the glass fiber. Furthermore, as required, a resin having a film-forming ability such as a fatty acid amide compound, a lubricant such as silicone oil, an antistatic agent such as a quaternary ammonium salt, an epoxy resin, a polyurethane resin, or a mixture of a resin having a film-forming ability and a heat stabilizer, a flame retardant, etc. may be used for surface treatment.

[0074] The content of the reinforcing fiber (preferably glass fiber) in the resin composition of the present embodiment is relative to 100 parts by mass of xylylenediamine-based polyamide resin, more than 10 parts by mass, preferably more than 15 parts by mass, more preferably more than 20 parts by mass, further preferably more than 30 parts by mass, and further can be more than 40 parts by mass. By being set to more than the aforementioned lower limit, there is a tendency that the mechanical strength of the obtained resin molding is further improved. In addition, the content of the reinforcing fiber (preferably glass fiber) in the resin composition of the present embodiment is relative to 100 parts by mass of xylylenediamine-based polyamide resin, less than 300 parts by mass, preferably less than 280 parts by mass, more preferably less than 250 parts by mass, further preferably less than 200 parts by mass, and further preferably less than 150 parts by mass, and further preferably less than 100 parts by mass, and further can be less than 90 parts by mass.

[0075] In addition, the content of the reinforcing fiber (preferably glass fiber) in the resin combination of the present embodiment is preferably more than 10 mass %, more preferably more than 15 mass %, more preferably more than 20 mass %, and can be more than 25 mass %.By being set to more than the aforementioned lower limit, there is a tendency that the mechanical strength of the resin molding obtained is further improved.In addition, the content of the reinforcing fiber (preferably glass fiber) in the resin combination of the present embodiment is preferably less than 50 mass %, more preferably less than 40 mass %, and can be less than 35 mass %.By being set to less than the above-mentioned upper limit, there is a tendency that the appearance of the molding obtained is further improved.

[0076] The resin composition of the present embodiment may contain only one type of reinforcing fiber, or may contain two or more types. When containing two or more types, the total amount is preferably within the above range.

[0077] <Impact-resistant modified materials>

[0078] The resin composition of the present embodiment may contain an impact resistance modifier.

[0079] As the impact resistance modifier, a wide range of impact resistance modifiers that can be compounded in thermoplastic resins can be used.

[0080] Another example of the impact resistance modifier is polyolefin, preferably acid-modified polyolefin. The use of acid-modified polyolefin can increase the crystallization rate.

[0081] The acid-modified polyolefin used in the present embodiment is obtained, for example, by acid-modifying a polyolefin. Acid modification means that an acid derivative is reacted with a polyolefin in any form. Specifically, the acid-modified polyolefin used in the present embodiment is obtained by grafting an acid derivative onto the main chain of a polyolefin or incorporating an acid derivative into the main chain of a polyolefin. In the present embodiment, the polyolefin is preferably a graft polymer in which an acid derivative is grafted onto the main chain of a polyolefin.

[0082] The acid derivative is preferably an acid or an anhydride, more preferably an unsaturated carboxylic acid or an anhydride of an unsaturated carboxylic acid, and still more preferably an anhydride of an unsaturated carboxylic acid. The unsaturated carboxylic acid is preferably an unsaturated dicarboxylic acid, and the anhydride of an unsaturated carboxylic acid is also preferably an anhydride of an unsaturated dicarboxylic acid.

[0083] As the acid derivative, maleic acid, maleic anhydride, itaconic acid, itaconic anhydride, 5-norbornene-2,3-dicarboxylic acid, 5-norbornene-2,3-dicarboxylic anhydride, norbornene dicarboxylic acid, endicanhydride, citraconic acid, citraconic anhydride, 1-butene-3,4-dicarboxylic acid, and 1-butene-3,4-dicarboxylic anhydride are more preferred, maleic acid and maleic anhydride are further preferred, and maleic anhydride is still more preferred.

[0084] The method of modifying the copolymer with an acid derivative can be carried out using a known technique without particular limitation. For example, the following methods can be used: a method of copolymerizing an acid derivative with a monomer serving as a raw material for the copolymer, a method of grafting an acid derivative onto the copolymer, etc.

[0085] In addition, in the resin composition of this embodiment, the xylylenediamine-based polyamide resin and the acid-modified polyolefin may be bonded to each other.

[0086] The acid-modified polyolefin is preferably obtained by acid-modifying a copolymer including a structural unit derived from ethylene and a structural unit derived from an α-olefin having 3 to 20 carbon atoms with an acid derivative. By forming such a structure, impact resistance can be more effectively improved.

[0087] The α-olefin having 3 to 20 carbon atoms is preferably an α-olefin having 3 to 10 carbon atoms, more preferably an α-olefin having 3 to 8 carbon atoms, further preferably an α-olefin having 3 to 5 carbon atoms, and still more preferably an α-olefin having 3 or 4 carbon atoms. Specific examples of the α-olefins having 3 to 20 carbon atoms include propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, 1-eicosene, 3-methyl-1-butene, 3-methyl-1-pentene, 3-ethyl-1-pentene, 4-methyl-1-pentene, 4-methyl-1-hexene, 4,4-dimethyl-1-hexene, 4,4-dimethyl-1-pentene, 4-ethyl-1-hexene, 3-ethyl-1-hexene, 9-methyl-1-decene, 11-methyl-1-dodecene, and 12-ethyl-1-tetradecene, and propylene and 1-butene are preferred.

[0088] The copolymer comprising structural units derived from ethylene and structural units derived from an α-olefin having 3 to 20 carbon atoms may contain only one type of repeating unit derived from an α-olefin having 3 to 20 carbon atoms, or may contain two or more types. The copolymer may be a random polymer or a block polymer.

[0089] The copolymer preferably contains structural units derived from an α-olefin having 3 to 20 carbon atoms in a ratio of 6 to 25 mol % of all structural units, more preferably 8 to 22 mol %, and even more preferably 10 to 20 mol %. Such a structure can more effectively improve impact resistance.

[0090] The copolymer preferably contains structural units derived from ethylene in a ratio of 94 to 75 mol %, more preferably 92 to 78 mol %, and even more preferably 90 to 80 mol % of all structural units.

[0091] Furthermore, the copolymer may contain other structural units in addition to the structural units derived from ethylene and the structural units derived from α-olefins having 3 to 20 carbon atoms. When the acid-modified polyolefin used in the present embodiment contains other structural units, the proportion is preferably 10 mol% or less of all the structural units in the copolymer.

[0092] Specific examples of the copolymer include ethylene / propylene copolymers, ethylene / butene copolymers, ethylene / hexene copolymers, ethylene / propylene / dicyclopentadiene copolymers, and ethylene / propylene / 5-ethylidene-2-norbornene copolymers, and ethylene / butene copolymers are preferred.

[0093] An example of the acid-modified polyolefin used in the present embodiment is a maleic anhydride-modified polyolefin, preferably an ethylene / propylene copolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, an ethylene / propylene / dicyclopentadiene copolymer or an ethylene / propylene / 5-ethylidene-2-norbornene copolymer modified with maleic anhydride.

[0094] The acid modification rate of the acid-modified polyolefin used in the present embodiment is preferably 0.3% by mass or more, more preferably 0.4% by mass or more, further preferably 0.5% by mass or more, further preferably 0.6% by mass or more, further preferably 0.8% by mass or more, and particularly preferably 0.9% by mass or more. By setting it to such a range, the impact resistance can be improved more effectively. On the other hand, as the upper limit of the acid modification rate, it is preferably 4.0% by mass or less, more preferably 3.5% by mass or less, further preferably 3.0% by mass or less, and further preferably 2.5% by mass or less. By setting it below the upper limit, there is a tendency for the dispersibility of the acid-modified polyolefin to be improved.

[0095] In addition, the modification rate by an acid derivative (acid modification rate) in this embodiment is measured according to the description of paragraph 0056 of JP-A-2018-087319.

[0096] Examples of commercially available products of the acid-modified polyolefin used in the present embodiment include TAFMER (trade name, graft polymer) manufactured by Mitsui Chemicals, FUSABOND (trade name) manufactured by DuPont, and Amplify (trade name) manufactured by TAU.

[0097] The content of the polyolefin in the resin composition of the present embodiment, when containing the polyolefin, is preferably 0.1 parts by mass or more, more preferably 1 part by mass or more, and is preferably 15 parts by mass or less, and further preferably 10 parts by mass or less, relative to 100 parts by mass of the xylylenediamine-based polyamide resin.

[0098] The resin composition of the present embodiment may contain only one type of polyolefin or may contain two or more types. When containing two or more types, the total amount is preferably within the above range.

[0099] <Crystallization-promoting agent>

[0100] The resin composition of the present embodiment may contain a crystallization-promoting auxiliary agent. By containing the crystallization-promoting auxiliary agent, the molding cycle of the resin composition can be further improved, and the crystallization speed of the resin composition can be accelerated.

[0101] An example of a crystallization-promoting auxiliary agent is a nucleating agent.

[0102] The nucleating agent may be any one of an organic nucleating agent and an inorganic nucleating agent, and is preferably an inorganic nucleating agent. Examples of the inorganic nucleating agent include graphite, molybdenum disulfide, barium sulfate, talc, mica, calcium carbonate, sodium phosphate, boron nitride, and kaolin, and preferably contains at least one selected from talc, mica, calcium carbonate, and boron nitride, more preferably contains at least one selected from talc and calcium carbonate, and further preferably contains talc.

[0103] When the resin composition of the present embodiment contains a nucleating agent, the content thereof is preferably 0.1 parts by mass or more, more preferably 0.2 parts by mass or more, and is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, and further preferably 3 parts by mass or less, relative to 100 parts by mass of the xylylenediamine-based polyamide resin.

[0104] Another example of the crystallization promoting aid is a carbon material. Examples of the carbon material include carbon black and carbon nanotubes.

[0105] When the resin composition of the present embodiment contains a carbon material, its content is preferably 0.1 parts by mass or more, more preferably 0.2 parts by mass or more, and is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, and further preferably 3 parts by mass or less, relative to 100 parts by mass of the xylylenediamine-based polyamide resin.

[0106] The resin composition of the present embodiment may contain only one type of crystallization accelerator, or may contain two or more types.

[0107] <Other ingredients>

[0108] The resin composition of the present embodiment may also contain other components within the scope of the present invention. As such additives, plasticizers, release agents, light stabilizers, antioxidants, ultraviolet absorbers, fluorescent brighteners, anti-dripping agents, antistatic agents, antifogging agents, anti-blocking agents, flowability improvers, plasticizers, dispersants, antibacterial agents, flame retardants, copper compounds, etc. can be cited.

[0109] In addition, in the resin composition of this embodiment, the content of the xylylenediamine-based polyamide resin, the reinforcing fiber, and other additives is adjusted so that the total of each component becomes 100 mass %.

[0110] <Physical properties of resin composition>

[0111] The resin composition of the present embodiment preferably has a high flexural modulus. Specifically, the resin composition of the present embodiment is molded into an ISO multi-purpose dumbbell test piece (4 mm thick), and the flexural modulus measured at a temperature of 23 ° C according to ISO178 is preferably more than 6.0 GPa, more preferably more than 6.5 GPa, further preferably more than 7.0 GPa, and further preferably more than 7.5 GPa. The upper limit of the flexural modulus is not particularly limited, and 10.0 GPa or less is practical.

[0112] The resin composition of the present embodiment preferably has a fast crystallization speed. Specifically, when the resin composition of the present embodiment is molded into an injection molded sheet having a thickness of 1 mmt at a mold temperature of 100° C. and crystallized, the molding cycle is preferably 50 seconds or less.

[0113] The details of the methods for measuring these physical properties are described in the examples described later.

[0114] <Method for producing resin composition>

[0115] The manufacture method of the resin combination of the present embodiment is not particularly limited, and is preferably a method using a single screw or twin screw extruder with a device that can devolatilize from a vent as a mixing mill. The above-mentioned xylylenediamine-based polyamide resin, reinforcing fibers and other additives compounded as required can be supplied to the mixing mill together, and other compounding components can also be supplied successively after the polyamide resin component is supplied. In addition, it is also possible to pre-mix the components selected from more than 2 kinds of each component and mix. Particularly reinforcing fibers are preferably side-fed.

[0116] The method for producing a molded article using the resin composition of the present embodiment is not particularly limited, and molding methods commonly used for thermoplastic resins, i.e., injection molding, blow molding, extrusion molding, press molding, etc., can be applied. In this case, from the viewpoint of good fluidity, a particularly preferred molding method is injection molding. During injection molding, the resin temperature is preferably controlled to 200 to 310°C.

[0117] <Application>

[0118] The molded article of the present embodiment is formed from the resin composition of the present embodiment.

[0119] The molded product of this embodiment can be widely used as an extrusion molded product or an injection molded product.

[0120] The molded product of this embodiment can also be applied to various storage containers, electrical / electronic equipment parts, precision equipment parts, office automation (OA) equipment parts, home appliance parts, mechanical mechanism parts, vehicle mechanism parts, etc. In particular, from the viewpoint of high strength, high impact resistance, high chemical resistance, low water absorption, and the ability to reduce the amount of eluted matter, it is suitable for connectors, tanks, ski boots, hydrogen tanks, etc. In addition, from the viewpoint of being able to perform crystallization in a mold at low temperature, it is also suitable for two-color molding with a relatively low melting point resin such as polyethylene.

[0121] Example

[0122] Hereinafter, the present invention will be further specifically described by enumerating examples. The materials, usage amounts, ratios, processing contents, processing steps etc. shown in the following examples may be appropriately changed without departing from the gist of the present invention. Therefore, the scope of the present invention is not limited to the specific examples shown below.

[0123] When the measuring equipment used in the examples is difficult to obtain due to discontinuation of production or the like, other equipment having equivalent performance may be used for measurement.

[0124] 1. Raw materials

[0125] The following polyamide resins were used.

[0126] <Synthesis Example 1 Synthesis of MP12 (30) (Relative Viscosity 2.1)>

[0127] In a jacketed reactor equipped with a stirrer, a partial condenser, a condenser, a thermometer, a dropping tank, and a nitrogen inlet tube, 59.60 mol of 1,12-dodecanedioic acid was accurately weighed and placed, and nitrogen replacement was performed thoroughly. Then, the temperature was raised to 180°C under a small amount of nitrogen flow to dissolve 1,12-dodecanedioic acid and form a uniform fluid state. Under stirring, 60.00 mol of p- / m-xylylenediamine, in which 30 mol% of the diamine components were p-xylylenediamine and 70 mol% were m-xylylenediamine, was added dropwise over 160 minutes. During this period, the internal pressure of the reaction system was set to normal pressure, and the internal temperature was continuously raised to 240°C. In addition, the water distilled out while dropping p- / m-xylylenediamine was discharged to the outside of the system through the partial condenser and the condenser. After the dropwise addition of p- / m-xylylenediamine was completed, the liquid temperature was maintained at 240°C and the reaction was continued for 10 minutes. After that, the pressure inside the reaction system was continuously reduced to 600 Torr within 10 minutes, and then the reaction was continued for 20 minutes. During this period, the reaction temperature was continuously raised to 250°C. After the reaction was completed, a pressure of 0.3 MPa was applied to the reactor under nitrogen, and the polymer was taken out from the nozzle at the bottom of the polymerization tank in the form of strands, and cut into pellets after water cooling to obtain pellets of the melt polymer product.

[0128] The obtained polyamide resin (MP12(30)) had a melting point of 206°C and a relative viscosity of 2.1.

[0129] <Synthesis Example 2 Synthesis of MP12 (40)>

[0130] In a jacketed reactor equipped with a stirrer, a partial condenser, a condenser, a thermometer, a dropping tank, and a nitrogen inlet tube, 59.60 mol of 1,12-dodecanedioic acid was accurately weighed and placed, and nitrogen replacement was performed thoroughly. Then, the temperature was raised to 180°C under a small amount of nitrogen flow to dissolve 1,12-dodecanedioic acid and form a uniform fluid state. Under stirring, 60.00 mol of p- / m-xylylenediamine, in which 40 mol% of the diamine components were p-xylylenediamine and 60 mol% were m-xylylenediamine, was added dropwise over 160 minutes. During this period, the internal pressure of the reaction system was set to normal pressure, and the internal temperature was continuously raised to 250°C. In addition, the water distilled while dropping p- / m-xylylenediamine was discharged to the outside of the system through the partial condenser and the condenser. After the dropwise addition of p- / m-xylylenediamine was completed, the liquid temperature was maintained at 250°C and the reaction was continued for 10 minutes. After that, the pressure inside the reaction system was continuously reduced to 600 Torr within 10 minutes, and then the reaction was continued for 20 minutes. During this period, the reaction temperature was continuously raised to 260°C. After the reaction was completed, a pressure of 0.3 MPa was applied to the reactor under nitrogen, and the polymer was taken out from the nozzle at the bottom of the polymerization tank in the form of strands, and cut into pellets after water cooling to obtain pellets of the melt polymerized product.

[0131] The obtained polyamide resin (MP12(40)) had a melting point of 216°C and a relative viscosity of 2.1.

[0132] <Synthesis Example 3 Synthesis of PXD12>

[0133] In a jacketed reactor equipped with a stirrer, a partial condenser, a condenser, a thermometer, a dropping tank, and a nitrogen inlet tube, 59.60 mol of 1,12-dodecanedioic acid was accurately weighed and placed, and nitrogen replacement was performed fully. Then, the temperature was raised to 180°C under a small amount of nitrogen flow to dissolve 1,12-dodecanedioic acid and form a uniform fluid state. Under stirring, 60.00 mol of p-phenylenediamine was added dropwise over 160 minutes. During this period, the internal pressure of the reaction system was set to normal pressure, and the internal temperature was continuously raised to 290°C. In addition, the water distilled while dropping p-phenylenediamine was discharged to the outside of the system through the partial condenser and the condenser. After the dropwise addition of p-phenylenediamine was completed, the liquid temperature was maintained at 290°C and the reaction was continued for 10 minutes. Thereafter, the internal pressure of the reaction system was continuously reduced to 600 Torr within 10 minutes, and then the reaction was continued for 20 minutes. During this period, the reaction temperature was continuously raised to 300°C. After the reaction was completed, a pressure of 0.3 MPa was applied to the reactor under nitrogen, and the polymer was taken out from the nozzle at the bottom of the polymerization tank in the form of a strand, and then cut into pellets after water cooling to obtain pellets of a molten polymer product.

[0134] The obtained polyamide resin (PXD12) had a melting point of 269° C. and a relative viscosity of 2.1.

[0135] <Synthesis Example 4 Synthesis of MXD12>

[0136] In a jacketed reactor equipped with a stirrer, a partial condenser, a condenser, a thermometer, a dropping tank, and a nitrogen inlet tube, 59.60 mol of 1,12-dodecanedioic acid was accurately weighed and placed, and nitrogen replacement was performed fully. Then, the temperature was raised to 180°C under a small amount of nitrogen flow to dissolve 1,12-dodecanedioic acid and form a uniform fluid state. Under stirring, 60.00 mol of meta-xylylenediamine was added dropwise over 160 minutes. During this period, the internal pressure of the reaction system was set to normal pressure, and the internal temperature was continuously raised to 230°C. In addition, the water distilled while dropping meta-xylylenediamine was discharged to the outside of the system through the partial condenser and the condenser. After the dropwise addition of meta-xylylenediamine was completed, the liquid temperature was maintained at 230°C and the reaction was continued for 10 minutes. Thereafter, the internal pressure of the reaction system was continuously reduced to 600 Torr within 10 minutes, and then the reaction was continued for 20 minutes. During this period, the reaction temperature was continuously raised to 240°C. After the reaction was completed, a pressure of 0.3 MPa was applied to the reactor under nitrogen, and the polymer was taken out from the nozzle at the bottom of the polymerization tank in the form of a strand, and then cut into pellets after water cooling to obtain pellets of a molten polymer product.

[0137] The obtained polyamide resin (MXD12) had a melting point of 186° C. and a relative viscosity of 2.1.

[0138] <Synthesis Example 5 Synthesis of MP14 (30)>

[0139] In a jacketed reactor equipped with a stirrer, a partial condenser, a condenser, a thermometer, a dropping tank, and a nitrogen inlet tube, 59.60 mol of 1,14-tetradecanedioic acid was accurately weighed and placed. The atmosphere was fully purged with nitrogen, and the temperature was raised to 180°C under a small amount of nitrogen flow to dissolve the 1,14-tetradecanedioic acid and form a uniform fluid state. Under stirring, 60.00 mol of p- / m-xylylenediamine, in which 30 mol% of the diamine components were p-xylylenediamine and 70 mol% were m-xylylenediamine, was added dropwise over 160 minutes. During this period, the internal pressure of the reaction system was set to normal pressure, and the internal temperature was continuously raised to 240°C. In addition, the water distilled out while dropping p- / m-xylylenediamine was discharged to the outside of the system through the partial condenser and the condenser. After the dropwise addition of p- / m-xylylenediamine was completed, the liquid temperature was maintained at 240°C and the reaction was continued for 10 minutes. After that, the pressure inside the reaction system was continuously reduced to 600 Torr within 10 minutes, and then the reaction was continued for 20 minutes. During this period, the reaction temperature was continuously raised to 250°C. After the reaction was completed, a pressure of 0.3 MPa was applied to the reactor under nitrogen, and the polymer was taken out from the nozzle at the bottom of the polymerization tank in the form of strands, and cut into pellets after water cooling to obtain pellets of the melt polymer product.

[0140] The obtained polyamide resin (MP14(30)) had a melting point of 200°C and a relative viscosity of 2.1.

[0141] <Synthesis Example 6 Synthesis of MP12 (30) (Relative Viscosity 1.8)>

[0142] In a jacketed reactor equipped with a stirrer, a partial condenser, a condenser, a thermometer, a dropping tank, and a nitrogen inlet tube, 58.50 mol of 1,12-dodecanedioic acid was accurately weighed and placed, and nitrogen replacement was performed thoroughly. Then, the temperature was raised to 180°C under a small amount of nitrogen flow to dissolve 1,12-dodecanedioic acid and form a uniform fluid state. Under stirring, 60.00 mol of p- / m-xylylenediamine, in which 30 mol% of the diamine components were p-xylylenediamine and 70 mol% were m-xylylenediamine, was added dropwise over 160 minutes. During this period, the internal pressure of the reaction system was set to normal pressure, and the internal temperature was continuously raised to 240°C. In addition, the water distilled out while dropping p- / m-xylylenediamine was discharged to the outside of the system through the partial condenser and the condenser. After the dropwise addition of p- / m-xylylenediamine was completed, the liquid temperature was maintained at 240°C and the reaction was continued for 10 minutes. After that, the pressure inside the reaction system was continuously reduced to 600 Torr within 10 minutes, and then the reaction was continued for 20 minutes. During this period, the reaction temperature was continuously raised to 250°C. After the reaction was completed, a pressure of 0.3 MPa was applied to the reactor under nitrogen, and the polymer was taken out from the nozzle at the bottom of the polymerization tank in the form of strands, and cut into pellets after water cooling to obtain pellets of the melt polymer product.

[0143] The obtained polyamide resin (MP12(30)) had a melting point of 206°C and a relative viscosity of 1.8.

[0144] <Synthesis Example 7 Synthesis of MP12 (30) (Relative Viscosity 2.5)>

[0145] In a jacketed reactor equipped with a stirrer, a partial condenser, a condenser, a thermometer, a dropping tank, and a nitrogen inlet tube, 60.00 mol of 1,12-dodecanedioic acid was accurately weighed and placed, and nitrogen replacement was performed thoroughly. Then, the temperature was raised to 180°C under a small amount of nitrogen flow to dissolve 1,12-dodecanedioic acid and form a uniform fluid state. Under stirring, 60.00 mol of p- / m-xylylenediamine, in which 30 mol% of the diamine components were p-xylylenediamine and 70 mol% were m-xylylenediamine, was added dropwise over 160 minutes. During this period, the internal pressure of the reaction system was set to normal pressure, and the internal temperature was continuously raised to 240°C. In addition, the water distilled while dropping p- / m-xylylenediamine was discharged to the outside of the system through the partial condenser and the condenser. After the dropwise addition of p- / m-xylylenediamine was completed, the liquid temperature was maintained at 240°C and the reaction was continued for 10 minutes. After that, the pressure inside the reaction system was continuously reduced to 600 Torr within 10 minutes, and then the reaction was continued for 20 minutes. During this period, the reaction temperature was continuously raised to 250°C. After the reaction was completed, a pressure of 0.3 MPa was applied to the reactor under nitrogen, and the polymer was taken out from the nozzle at the bottom of the polymerization tank in the form of strands, and cut into pellets after water cooling to obtain pellets of the melt polymer product.

[0146] The obtained polyamide resin (MP12(30)) had a melting point of 206°C and a relative viscosity of 2.5.

[0147] <Synthesis Example 8 Synthesis of MP10 (30) (Relative Viscosity 2.5)>

[0148] In a jacketed reactor equipped with a stirrer, a partial condenser, a condenser, a thermometer, a dropping tank and a nitrogen inlet tube, 60.00 mol of accurately weighed sebacic acid was placed, nitrogen replacement was fully performed, and then the temperature was raised to 180°C under a small amount of nitrogen flow to dissolve the sebacic acid and form a uniform flow state. Under stirring, 60.00 mol of p- / m-phenylenediamine, in which 30 mol% of the diamine components were p-phenylenediamine and 70 mol% were m-phenylenediamine, was added dropwise over 160 minutes. During this period, the internal pressure of the reaction system was set to normal pressure, and the internal temperature was continuously raised to 250°C. In addition, the water distilled while dropping p-phenylenediamine was discharged to the outside of the system through the partial condenser and condenser. After the dropwise addition of p-phenylenediamine was completed, the liquid temperature was maintained at 250°C and the reaction was continued for 10 minutes. Thereafter, the internal pressure of the reaction system was continuously reduced to 600 Torr within 10 minutes, and then the reaction was continued for 20 minutes. During this period, the reaction temperature was continuously raised to 260° C. After the reaction was completed, a pressure of 0.3 MPa was applied to the reactor under nitrogen, and the polymer was taken out from the nozzle at the bottom of the polymerization tank in the form of strands, and then cut into pellets after water cooling to obtain pellets of the melt polymer product.

[0149] The obtained polyamide resin (MP10) had a melting point of 215° C. and a relative viscosity of 2.5.

[0150] <Synthesis Example 9 Synthesis of MP10 (30) (Relative Viscosity 2.1)>

[0151] In a jacketed reactor equipped with a stirrer, a partial condenser, a condenser, a thermometer, a dropping tank and a nitrogen inlet tube, 59.60 mol of sebacic acid was accurately weighed, and nitrogen replacement was performed fully. Then, the temperature was raised to 180°C under a small amount of nitrogen flow to dissolve the sebacic acid and form a uniform flow state. Under stirring, 60.00 mol of p- / m-phenylenediamine, in which 30 mol% of the diamine components were p-phenylenediamine and 70 mol% were m-phenylenediamine, was added dropwise over 160 minutes. During this period, the internal pressure of the reaction system was set to normal pressure, and the internal temperature was continuously raised to 250°C. In addition, the water distilled while dropping p-phenylenediamine was discharged to the outside of the system through the partial condenser and condenser. After the dropwise addition of p-phenylenediamine was completed, the liquid temperature was maintained at 250°C and the reaction was continued for 10 minutes. After that, the internal pressure of the reaction system was continuously reduced to 600 Torr within 10 minutes, and then the reaction was continued for 20 minutes. During this period, the reaction temperature was continuously raised to 260° C. After the reaction was completed, a pressure of 0.3 MPa was applied to the reactor under nitrogen, and the polymer was taken out from the nozzle at the bottom of the polymerization tank in the form of strands, and then cut into pellets after water cooling to obtain pellets of the melt polymer product.

[0152] The obtained polyamide resin (MP10(30)) had a melting point of 215°C and a relative viscosity of 2.1.

[0153] PA12: Polyamide 12, manufactured by UBE, product number: UBESTA3024U

[0154] PA6: Polyamide 6, manufactured by UBE, product number: UBE NYLON 1022B

[0155] <Method for measuring relative viscosity>

[0156] The relative viscosity of the polyamide resin is measured in accordance with JIS K6933:2013 (ISO 307:2007).

[0157] <Terminal amino group concentration (μmol / g)>

[0158] (a) Terminal amino group concentration ([NH2] μmol / g)

[0159] 0.2 to 0.5 g of polyamide resin was accurately weighed and dissolved in 30 mL of a phenol / ethanol = 4 / 1 volumetric solution under stirring. After the polyamide was completely dissolved, neutralization titration was performed with N / 100 hydrochloric acid to determine the molecular weight.

[0160] (b) Terminal carboxyl concentration ([COOH] μmol / g)

[0161] 0.2 to 0.5 g of polyamide resin was accurately weighed, and the polyamide was dissolved in 30 mL of benzyl alcohol under nitrogen flow at 160 to 180° C. and stirred. After the polyamide was completely dissolved, it was cooled to 80° C. under nitrogen flow, 10 mL of methanol was added while stirring, and neutralization titration was performed with N / 100 sodium hydroxide aqueous solution to obtain the polyamide.

[0162] The following materials were used as reinforcing fibers and polyolefins.

[0163] Reinforcement fiber: T-275GH, made by Nippon Electric Glass Co., Ltd., glass fiber

[0164] Impact resistance modifier: TAFMER MH5020, maleic anhydride-modified ethylene-butene copolymer, manufactured by Mitsui Chemicals, Inc., maleic anhydride modification rate: 1.0 mass%

[0165] 2. Examples 1 to 11, Comparative Examples 1 to 5

[0166] <Compound>

[0167] Each component was weighed in a manner to form the composition shown in Tables 1 to 3 described later, and each component was blended in a drum and fed from the bottom of a twin-screw extruder (TEM26SS manufactured by Shibaura Machine Co., Ltd.). In addition, for glass fiber, a vibrating type cassette welding feeder (CE-V-1B-MP manufactured by KUBOTA Corporation) was used to feed the glass fiber from the side of the extruder into the above-mentioned twin-screw extruder, and melt-kneaded with the resin component, etc. to obtain a resin composition pellet. The temperature setting of the twin-screw extruder was set to 240 to 280°C.

[0168] <Molding cycle>

[0169] The pellets obtained by the above-mentioned production method were dried at 120°C for 4 hours and then injection molded into a three-stage plate in an injection molding machine (NEX140III manufactured by Nissei Plastic Industry Co., Ltd.) at a cylinder temperature of 200 to 300°C and a mold temperature of 100°C.

[0170] When the molding cycle is short, it can be said that the crystallization speed is fast.

[0171] Evaluation was performed as described below.

[0172] 5: For a 1mm thick molded piece of a three-level plate, the molding cycle during in-mold crystallization is less than 50 seconds

[0173] 1: For a 1mm thick molded piece of a three-level plate, the molding cycle during in-mold crystallization is longer than 50 seconds

[0174] <Appearance>

[0175] The pellets obtained by the above-mentioned manufacturing method were dried at 120°C for 4 hours and then injection molded into a three-stage plate in an injection molding machine (NEX140III manufactured by Nissei Plastic Industry Co., Ltd.) under the conditions of a cylinder temperature of 200 to 300°C, a mold temperature of 100°C, and a molding cycle of 50 seconds. The criterion of "3: The appearance of the molded sheet with a thickness of 1 mmt is good" was used as Example 10, and judgment was made by 5 experts, and a majority decision was made.

[0176] Evaluation was performed as described below.

[0177] 5: The appearance of the molded piece with a thickness of 1mmt is very good

[0178] 3: The appearance of the molded piece with a thickness of 1mmt is good

[0179] 1: The appearance of the molded piece with a thickness of 1mmt is poor

[0180] <Flexural modulus>

[0181] The pellets obtained by the above-mentioned manufacturing method were dried at 120°C for 4 hours and then injection molded into ISO multi-purpose dumbbell test pieces (4 mm thick) in an injection molding machine (manufactured by Nissei Plastic Industry Co., Ltd., "NEX140III") under the conditions of a barrel temperature of 200-300°C, a mold temperature of 130°C, and a molding cycle of 50 seconds.

[0182] Flexural modulus was measured at 23°C according to ISO178 (unit: GPa)

[0183] Evaluation was performed as described below.

[0184] 5: More than 7.5GPa

[0185] 4: More than 7.0 GPa and less than 7.5 GPa

[0186] 3: More than 6.5 GPa and less than 7.0 GPa

[0187] 2: More than 6.0 GPa and less than 6.5 GPa

[0188] 1: Below 6.0GPa

[0189] <Impact resistance>

[0190] The pellets obtained by the above-mentioned manufacturing method were dried at 120°C for 4 hours and then injection molded into ISO multi-purpose dumbbell test pieces (4 mm thick) in an injection molding machine (manufactured by Nissei Plastic Industry Co., Ltd., "NEX140III") under the conditions of a barrel temperature of 200-300°C, a mold temperature of 130°C, and a molding cycle of 50 seconds.

[0191] According to ISO179 standard, Charpy impact strength (unnotched, unit: kJ / m 2 ) determination.

[0192] Evaluation was performed as described below.

[0193] 5: more than 60kJ / m 2

[0194] 4: more than 55kJ / m 2 And 60kJ / m 2 the following

[0195] 3: More than 50kJ / m 2 And 55kJ / m 2 the following

[0196] 2: More than 45kJ / m 2 And 50kJ / m 2the following

[0197] 1: more than 45kJ / m 2

[0198] <Gas Barrier Properties>

[0199] The pellets obtained by the above-mentioned manufacturing method were dried at 120°C for 4 hours and then injection molded into flat test pieces (2 mm thick) in an injection molding machine (manufactured by Nissei Plastic Industry Co., Ltd., "NEX140III") under the conditions of a cylinder temperature of 200-300°C, a mold temperature of 130°C, and a molding cycle of 50 seconds.

[0200] In an aluminum cup of Φ38 mm, 15 cc of a mixed solvent containing toluene (45 volume %), isooctane (45 volume %) and ethanol (10 volume %) was placed, a flat test piece was placed on the seal, and the seal and an aluminum lid with a hole of the same size as the mouth of the cup were installed and tightened.

[0201] The gas permeability coefficient (g·mm / m 2 ·day).

[0202] Gas permeability coefficient (g·mm / m 2 ·day) = [(mass before storage - mass after storage) × (thickness of test piece)] / [(area of ​​the mouth of the aluminum cup) × (number of days of storage)]

[0203] Evaluation was performed as described below.

[0204] 5:2(g·mm / m 2 ·day) or less

[0205] 4: More than 2 (g mm / m 2 ·day) and 4(g·mm / m 2 ·day) or less

[0206] 3: More than 4 (g mm / m 2 ·day) and 6(g·mm / m 2 ·day) or less

[0207] 2: More than 6 (g mm / m 2 ·day) and 10(g·mm / m 2 ·day) or less

[0208] 1: more than 10 (g mm / m 2 ·day)

[0209] <Amount of dissolved matter>

[0210] The pellets obtained by the above-mentioned manufacturing method were dried at 120°C for 4 hours and then injection molded into flat test pieces (2 mm thick) in an injection molding machine (manufactured by Nissei Plastic Industry Co., Ltd., "NEX140III") under the conditions of a cylinder temperature of 200-300°C, a mold temperature of 130°C, and a molding cycle of 50 seconds.

[0211] In an aluminum cup of Φ38 mm, 15 cc of a mixed solvent containing toluene (45% by volume), isooctane (45% by volume), and ethanol (10% by volume) was placed, a flat test piece was placed on the seal, and the seal and an aluminum lid having a hole of the same size as the mouth of the cup were installed and tightened. The liquid in the cup after the test after being stored in a thermostatic bath at 60°C for 1000 hours was filtered (filter paper: PTFE, pore size 50 μm), and the mass of the obtained solid elution was measured.

[0212] Evaluation was performed as described below.

[0213] 5: Less than 1 mg

[0214] 4: More than 1mg and less than 3mg

[0215] 3: More than 3 mg and less than 6 mg

[0216] 2: More than 6 mg and less than 10 mg

[0217] 1: more than 10mg

[0218] <Chemical resistance>

[0219] The pellets obtained by the above-mentioned manufacturing method were dried at 120°C for 4 hours and then injection molded into ISO multi-purpose dumbbell test pieces (4 mm thick) in an injection molding machine (manufactured by Nissei Plastic Industry Co., Ltd., "NEX140III") under the conditions of a barrel temperature of 200-300°C, a mold temperature of 130°C, and a molding cycle of 50 seconds.

[0220] The flexural modulus (unit: GPa) was measured at a temperature of 23°C in accordance with ISO 178.

[0221] The sample was immersed in 10 mass % hydrochloric acid for 7 days, and the flexural modulus was measured again. The ratio (%) of the flexural modulus after the immersion in hydrochloric acid to the initial flexural modulus was taken as the flexural modulus retention rate.

[0222] Evaluation was performed as described below.

[0223] 5: More than 80%

[0224] 4: 70% or more and less than 80%

[0225] 3: 60% or more and less than 70%

[0226] 2: 50% or more and less than 60%

[0227] 1: Less than 50%

[0228] <Water absorption>

[0229] The pellets obtained by the above-mentioned manufacturing method were dried at 120°C for 4 hours and then injection molded into ISO multi-purpose dumbbell test pieces (4 mm thick) in an injection molding machine (manufactured by Nissei Plastic Industry Co., Ltd., "NEX140III") under the conditions of a barrel temperature of 200-300°C, a mold temperature of 130°C, and a molding cycle of 50 seconds.

[0230] The samples were immersed in water for 120 days, and the ratio (%) of the difference between the mass after immersion in water and the initial mass to the initial mass was taken as the water absorption rate.

[0231] Water absorption (%) = [(mass after water immersion - initial mass) / initial mass] × 100

[0232] Evaluation was performed as described below.

[0233] 5: Below 1%

[0234] 4: More than 1% and less than 2%

[0235] 3: More than 2% and less than 3%

[0236] 2: More than 3% and less than 4%

[0237] 1: More than 4%

[0238] [Table 1]

[0239]

[0240] [Table 2]

[0241]

[0242] [Table 3]

[0243]

[0244] In Tables 1 to 3 above, the contents of the reinforcing fiber and the impact resistance modifier are the contents (mass %) of the reinforcing fiber and the impact resistance modifier, respectively, when the total amount of the resin composition is 100 mass %.

[0245] The above results show that when the resin composition of the present invention is formed into a molded article, the molding cycle is fast and the obtained molded article is also excellent in appearance (Examples 1 to 10).

[0246] In contrast, when the relative viscosity of the polyamide resin was high (Comparative Example 1), the appearance of the obtained molded product was poor. In addition, when a xylylenediamine-based polyamide resin (MP10) other than the specified xylylenediamine-based polyamide resin was used as the polyamide resin (Comparative Examples 2 and 3), the molding cycle was poor regardless of the relative viscosity.

[0247] In addition, when an aliphatic polyamide resin was used (Comparative Examples 4 and 5), the obtained molded article had poor appearance.

Claims

1. A resin composition comprising 10 to 300 parts by mass of reinforcing fibers relative to 100 parts by mass of a xylylenediamine-based polyamide resin, The xylylenediamine-based polyamide resin comprises a diamine unit and a dicarboxylic acid unit, wherein the diamine unit comprises 70 mol% or more of a structural unit derived from xylylenediamine, and the dicarboxylic acid unit comprises 70 mol% or more of a structural unit derived from an α,ω-straight-chain aliphatic dicarboxylic acid having 11 to 20 carbon atoms, and The relative viscosity of the xylylenediamine polyamide resin is 1.6 to 2.

4.

2. The resin composition according to claim 1, wherein More than 70 mol % of the dicarboxylic acid units are derived from dodecanedioic acid and / or tetradecanedioic acid.

3. The resin composition according to claim 1, wherein More than 70 mol % of the dicarboxylic acid units are derived from dodecanedioic acid.

4. The resin composition according to any one of claims 1 to 3, wherein 20 to 100 mol % of the diamine units are derived from m-xylylenediamine, and 80 to 0 mol % are derived from p-xylylenediamine.

5. The resin composition according to claim 1, wherein More than 70 mol % of the dicarboxylic acid units are derived from dodecanedioic acid and / or tetradecanedioic acid, 20 to 100 mol % of the diamine units are derived from m-xylylenediamine, and 80 to 0 mol % are derived from p-xylylenediamine.

6. The resin composition according to any one of claims 1 to 5, wherein The difference between the terminal amino group concentration and the terminal carboxyl group concentration of the xylylenediamine-based polyamide resin, ie, |terminal amino group concentration−terminal carboxyl group concentration|, is 10 μmol / g or more. 7 . A molded article formed from the resin composition according to claim 1 .

Citation Information

Patent Citations

  • Resin composition, molded article, and method for producing molded article

    JP2018087319A

  • Production method of polyamide resin

    JP2018165298A

  • Resin composition, molded article and thin wall molded article manufacturing method

    JP2022054099A